Pola Pertumbuhan Ayam Silangan Pelung Sentul Kampung Ras Pedaging (IPB D-1) G4 Umur 1-12 Minggu - Habiburahman, R.; Darwati, S.; Sumantri, C. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
Kampung chicken is a local Indonesian chicken that comes from red jungle chicken that has been successfully domesticated but has a low productivity. One of method to increase the productivity can be done by crossing a local chicken with a broiler. This research was conducted to examine the growth performance of crossing result G3 interse (pelung, sentul, kampung, broiler) age 1-12 weeks. IPB D-1 G3 chicken measured in this research were 76 DOC, 18 cocks, and 30 hens. T test was used to knowing the differences of body weight, body weight gain, feed consumption, and feed conversion. Based on the research, body weight, growth, and feed conversion of male IPB D-1 chickens was better than female IPB D-1 chickens when 12 weeks age. Body weight of a cock IPB D-1 G4 in 12 week was 1939.9 g and for a hen was 994.9 g. Feed consumption of rooster IPB D-1 G4 3 468.97 g and 3 339.80 in females with fluctuating body weight growth. Chicken feed conversion IPB D-1 lowest G4 1.579 and 6.430 with the highest. Coefficient of variation on all variables IPB D-1 G4 was high. Performance growth of IPB D-1 G4 still diverse.